Quality of life of Non-Permanent Teachers and Their Coping Strategies During the Covid-19 Pandemic - Decin, Zaila; Guinto, Adrian; Nachor, Arianne Nicole; Oabel, Diane April (Social Sciences and Development Review, 2023)
The COVID-19 pandemic has resulted in tremendous challenges. Education is among the most affected social sectors. Teachers and students are compelled to adapt to the alternative modes of teaching and learning delivery. The Philippines’ largest Higher Education Institution in terms of students became the focus of this study, particularly its non-permanent teaching staff. This research is designed to determine the quality of life and coping strategies of non-permanent teachers of the Polytechnic University of the Philippines during the COVID-19 pandemic. Using mixed methods – sequential explanatory research design, 278 respondents were selected out of the 1,926 total population. Quantitative data were collected through the use of the World Health Organization’s Quality of Life-BREF (WHOQOL-BREF) Scale and the Filipino Coping Strategies Scale (FCSS) and were analyzed using the Mann-Whitney U test, Kruskal-Wallis H test, and Pearson Product Moment Correlation. Meanwhile, qualitative data were collected through a validated and pilot-tested focus group discussion (FGD) guide with transcripts subjected to content analysis. Data revealed that the lowest dimension of quality of life of the teachers is the physical aspect. Some of the most common coping strategies were cognitive reappraisal, problem solving, religiosity, and relaxation. The respondents differ in terms of religiosity, relaxation, emotional release, and overactivity along with their age, other sources of income, and marital status. Further analysis indicated a relationship between the four domains of quality of life and some types of coping strategies which showed how the quality of life is affected by specific coping practices. Recommendations as to policies and programs to address the issues identified were set.
Keywords: challenges; coping strategies; COVID-19; quality of life; new normal; non-permanent teachers; pandemic